Development of Islamic Bank Performance Measurement Using The Maslahah Performa (MaP) Approach - Syahdatul Maulida; Achmad Firdaus (Islamiconomic : Jurnal Ekonomi Islam, 2025)
The objective of the research is to develop a performance measurement model for Islamic banks using the Maslahah Performa (MaP) approach. The performance measurement model encompasses six MaP maslahah orientations, namely worship, internal processes, talent, learning, customers, and wealth, with each maslahah orientation comprising specific measures, formulas, and targets. The development of performance measures is informed by a comprehensive array of sources, including the Qur'an and Hadith, financial statements, sustainability reports, Islamic bank governance, and regulations established by the OJK and Bank Indonesia. The research design entailed an exploratory study, wherein secondary data was obtained from financial reports, sustainability reports, Islamic bank governance reports, OJK and Bank Indonesia regulations, and other sources. Data samples were obtained from the annual reports of Bank Syariah Indonesia and Bank Muamalat. The selection of these two banks was made with the consideration that they can represent the classification of the Bank Group Based on Tier 1 Capital (KBMI). The findings from the data analysis were then used to develop a more comprehensive understanding of the application of maqashid sharia in measuring the performance of Islamic banks. The implications of this study for Islamic banking practitioners are that the application of the MaP model can help make more maqashid sharia-based decisions, ensuring a balance between profitability and social sustainability. Moreover, the findings of this study can serve as a foundation for regulators to formulate policies and regulations that more effectively support the integration of maqashid sharia principles in the performance assessment of Islamic banks.